2015
DOI: 10.1097/dbp.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Behavior Rating Inventory of Executive Function and Child Behavior Checklist in Ugandan Children with HIV or a History of Severe Malaria

Abstract: Objective To assess the structural overlap between the Behavior Rating Inventory of Executive Function (BRIEF) and Achenbach Child Behavior Check List (CBCL) among children in Uganda. Methods Caregiver ratings for the BRIEF and CBCL were obtained for two independent samples of school-aged children: 106 children (5-12 years old, 50% males) with a history of severe malaria, and on 144 HIV-infected children (5-12 years old, 58% males) in Uganda. Exploratory factor analysis was used to evaluate the factor struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
0
26
0
2
Order By: Relevance
“…The CBCL and BRIEF yield T-Scores (mean 5 50 and standard deviation 5 10). 21 Standard scores for SB-5 and DAS-II were used (mean 5 100 and standard deviation 5 15). 22 The diagnosis of ADHD was made by the psychologist or the pediatrician in the medical home using the Vanderbilt test.…”
Section: School-agementioning
confidence: 99%
“…The CBCL and BRIEF yield T-Scores (mean 5 50 and standard deviation 5 10). 21 Standard scores for SB-5 and DAS-II were used (mean 5 100 and standard deviation 5 15). 22 The diagnosis of ADHD was made by the psychologist or the pediatrician in the medical home using the Vanderbilt test.…”
Section: School-agementioning
confidence: 99%
“…For this study, we chose four Western-developed standard tests, previously used in LMIC HIV/AIDS and other high burden illness settings, These measures have proven sensitive to the neuropsychological effects of pediatric HIV in the sub-Saharan African context, assessing aspects of motor development and proficiency, attention, working memory, learning, visual-spatial analysis and problem solving, and planning and reasoning 1116 . The present study used the Kaufman Assessment Battery for Children, 2nd edition (KABC-II) 17 , the Test of Variables of Attention (TOVA; www.tovatest.com) 18 , the Bruininks-Oseretsky Test of Motor Proficiency, 2 nd edition (BOT-2) 19 , and the Behavior Rating Inventory for Executive Function (BRIEF) 20 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that HIV-affected depressed mothers in this setting are more likely to report child emotional and behavioral problems. 47, 48 In the present study, significantly higher reported behavior problems on the BRIEF-P for MISC children at one-year follow-up could have been due to MISC training resulting in increased caregiver sensitivity to their children’s behavior and their own behavioral expectations of their children compared to the health and nutrition focused curriculum.…”
Section: Discussionmentioning
confidence: 53%